Moral functioning across training and competition in sport - van de Pol, P. K. C.; Kavussanu, M.; Claessens, B. (International Journal of Sport and Exercise Psychology, 2020)
This study examined whether (a) adolescent (Mage = 15.13, SD = 1.55) team-sport athletes` (N = 137) perceived motivational climate, moral disengagement, and prosocial and antisocial behaviour differ in training and competition contexts, (b) moral disengagement mediates the relationship between motivational climate and prosocial and antisocial behaviour in training and competition, and (c) indirect effects between motivational climate, moral disengagement, and prosocial and antisocial behaviour are moderated by context. Repeated measures ANOVA revealed that athletes reported higher performance climate and antisocial behaviour in competition than in training, whereas mastery climate, moral disengagement and prosocial behaviour did not differ between contexts. Moderated mediation analysis revealed that the relationships between mastery climate and antisocial behaviour, and between performance climate and antisocial behaviour, were both mediated by moral disengagement in both contexts. No mediation effect was moderated by context. The findings of this study contribute to a better understanding of personal and contextual influences on athletes` moral functioning in sport. Keywords: morality, motivational climate, moral disengagement, fair play, sport